Regional Characteristics of Hospital Admissions and Outpatients Visits with Arterial Hypertension from the Point of the WHO Concept of Ambulatory Care Sensitive Conditions - A. V. Kontsevaya; Yu. V. Doludin; M. B. Khudyakov; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2020)
Aim. To analyze hospital admission and ambulatory care of the patients with arterial hypertension (AH) in federal districts and regions from the perspective of the WHO concept of diseases, which can be treated in ambulatory settings (ambulatory care sensitive conditions, ACSC).Material and methods. For analysis we used data from annual forms of federal statistical monitoring (12 and 14), which includes data on hospital admissions with hypertension in federal districts and separate regions in 2017. Hypertension included diseases characterized by raised blood pressure, ICD10: I10-I13.Results. We performed the analysis of 12 and 14 forms per districts and regions of the Russian Federation. Regions with increased hospitalization rates and an increased ratio of the hospitalizations to number to outpatients visits were identified. High variability of these indicators was observed both among both between regions and federal districts. The values of the ratio indicator vary from 0.0131 in the Nizhny Novgorod Region to 0.0234 in the Chechen Republic. The average value of the ratio in the federal district varies from 0.032 in the Volga Federal District to 0.119 in the North Caucasus Federal District. In the North Caucasus and Far East Federal District the value of the indicator is significantly higher than in other districts.Conclusion. Assessing diseases which can be treated in ambulatory setting scan be one of the tools for evaluating the quality of medical care in primary care facilities. However, before including ACSC as an indicator of the quality of health care delivery, a deeper understanding of the reasons that can impact its rates is required.